1999
DOI: 10.1094/phyto.1999.89.10.902
|View full text |Cite
|
Sign up to set email alerts
|

A Corn Trypsin Inhibitor with Antifungal Activity Inhibits Aspergillus flavus α-Amylase

Abstract: In this study, we found that the inhibition of fungal growth in potato dextrose broth (PDB) medium by the 14-kDa corn trypsin inhibitor (TI) protein, previously found to be associated with host resistance to aflatoxin production and active against various fungi, was relieved when exogenous alpha-amylase was added along with TI. No inhibitory effect of TI on fungal growth was observed when Aspergillus flavus was grown on a medium containing either 5% glucose or 1% gelatin as a carbon source. Further investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 34 publications
2
55
0
4
Order By: Relevance
“…The results obtained using conidial germination and hyphal growth was in correlation to each other as the results showed inhibition in the presence of trypsin inhibitor were consistent (Figures 7 and 8). These studies were similar to Chen et al [21] reports, which showed that the resistance of certain corn genotypes to fungal infection is related to the action of trypsin inhibitor, which is due to the lowering in the production and activity of fungal alpha-amylase, which in turn reduce the availability of simple sugars for fungal growth. Similar studies on the inhibition of spore germination and mycelium growth of Alternaria alternata by buckwheat trypsin/chymotrypsin was observed [22].…”
Section: Effect Of Anion Exchange Fractionssupporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained using conidial germination and hyphal growth was in correlation to each other as the results showed inhibition in the presence of trypsin inhibitor were consistent (Figures 7 and 8). These studies were similar to Chen et al [21] reports, which showed that the resistance of certain corn genotypes to fungal infection is related to the action of trypsin inhibitor, which is due to the lowering in the production and activity of fungal alpha-amylase, which in turn reduce the availability of simple sugars for fungal growth. Similar studies on the inhibition of spore germination and mycelium growth of Alternaria alternata by buckwheat trypsin/chymotrypsin was observed [22].…”
Section: Effect Of Anion Exchange Fractionssupporting
confidence: 89%
“…Likewise, cysteine proteinase inhibitors from pearl millet also inhibited the growth of many pathogenic fungi including Trichoderma reesei [23]. In addition, the antifungal effect of trypsin inhibitor was observed in wheat kernel [24], corn [21], barley [25] and cabbage [26].…”
Section: Effect Of Anion Exchange Fractionsmentioning
confidence: 99%
“…Transgenic cotton expressing the chloroperoxide or D4E1 genes showed antifungal activity against Aspergillus flavus and Verticillium dahliae [39] . The expression of 14-kDa Corn trypsin inhibitor gene was also showed resistance to A. flavus [40] . Similar to the above attempt, transgenic cotton plants harboring Talaromyces flavus GO gene results notable resistance against root pathogen Verticillium dahliae [41] .…”
Section: Expression Of Chitinasementioning
confidence: 94%
“…The mode of action of TI against fungal growth may be partially due to its inhibition of fungal -amylase, limiting A. flavus access to simple sugars [44] required not only for fungal growth, but also for toxin production [45]. TI also demonstrated antifungal activity against other mycotoxigenic species [46].…”
Section: Resistance-associated Proteinsmentioning
confidence: 99%